Academic content collection. Level A ([United Kingdom] : Thomson Heinle, 2007)
Collection of 6 stories of level A reader for practice and reinforcement
The Pilgrims Melanie Ann Apel -- Rain forest Melissa Cole -- The Hopi Marla Ryan (editor) -- How do i become a firefighter Mindi Englart -- The Solar system Don Nardo -- Frida Kahlo Kristen Woronoff
Title from container
Keywords: Kahlo, Frida -- Juvenile literature; Reading; Rain forest ecology -- Juvenile literature; Hopi Indians -- Juvenile literature; Fire fighters -- Juvenile literature; Solar system -- Juvenile literature; Pilgrims (New Plymouth Colony) -- Juvenile literature; Painters -- Mexico -- Biography -- Juvenile literature